-6-7=6x+10-5x

Simple and best practice solution for -6-7=6x+10-5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6-7=6x+10-5x equation:


Simplifying
-6 + -7 = 6x + 10 + -5x

Combine like terms: -6 + -7 = -13
-13 = 6x + 10 + -5x

Reorder the terms:
-13 = 10 + 6x + -5x

Combine like terms: 6x + -5x = 1x
-13 = 10 + 1x

Solving
-13 = 10 + 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-13 + -1x = 10 + 1x + -1x

Combine like terms: 1x + -1x = 0
-13 + -1x = 10 + 0
-13 + -1x = 10

Add '13' to each side of the equation.
-13 + 13 + -1x = 10 + 13

Combine like terms: -13 + 13 = 0
0 + -1x = 10 + 13
-1x = 10 + 13

Combine like terms: 10 + 13 = 23
-1x = 23

Divide each side by '-1'.
x = -23

Simplifying
x = -23

See similar equations:

| -32+5(12)= | | 1-n-2n=1-2n-n | | -32+5(4)= | | 3.29=3x-7 | | 1/2t-3/4=11/8 | | 2n-n=2n-3n | | 8x+1-7x=10 | | 6x+132=2x+15 | | 18+27x+15x^2=0 | | 7x+7-2x=2 | | 6x+(-6x)+10=1 | | 4j=18.92 | | 7.5m+15=75 | | 42-2(x)=4 | | -6=6x-7x+3 | | c-11=4 | | 0.8r=6.4 | | -x-6+4x=24 | | (8x-42)= | | 4(m+1)=6m+1 | | j/2=2.5 | | 2x+8+2x=28 | | Y-1/4=-4/5 | | 50-4(x)=2 | | Kx^2-20x+6k+1=0 | | 50-4(8)= | | 26(4+8)= | | 2x+75=6x+55 | | 50-4(2)= | | 6(3x+9)=108 | | dy/dx=(4y-3x)/x^2 | | 12.5m=75 |

Equations solver categories